Donor Site Morbidity of Calcaneal, Distal and Proximal Tibial Cancellous Autografts in Foot and Ankle Surgery: A Systematic Review and Meta-Analysis of 2296 Grafts. Issue 1 (January 2022) - Attia, Ahmed K.; Khamis, Karim Mahmoud; Elsweify, Kareem Ahmed H.M.A.; Bariteau, Jason T.; Labib, Sameh A.
Category: Other Introduction/Purpose: Non-union of foot and ankle arthrodesis sites has been associated with revision surgery, morbidity and increased healthcare costs, so many surgeons elect to augment the fusion site with autologous bone grafts to improve union. While iliac crest autografts are considered the historical gold standard, other donor sites distal in the lower extremity such as calcaneus, proximal and distal tibia have been successfully used in foot and ankle surgery. This study aims to report on the safety and donor site morbidity of distal lower extremity (calcaneal, proximal and distal tibial) bone autografts. We summarized the findings in a comprehensive infographic illustration. We are unaware of any similar meta-analyses to date. Methods: Following the PRISMA guidelines, 2 independent investigators searched several databases in December 2020 using the following keywords and their synonyms: ('Bone graft', 'donor site morbidity', 'calcaneal graft', 'Proximal tibia graft', and 'distal tibia graft'). Besides, the reference lists from previous review articles were searched manually for eligible studies. The primary outcomes of interest were (1) Chronic pain, (2) Fracture and (3) infection whereas the secondary outcomes were (1) neurological complications, (2) sensory disturbance and hypertrophic scars, (3) other complications such as shoe-wear difficulties and gait disturbance. Inclusion criteria were: studies on complications and adverse events of lower extremity bone autografts (calcaneal, proximal tibial, and distal tibial bone autografts) reporting at least one desired outcome. Studies not reporting any of the outcomes of interest or if the full text is not available in English were excluded. Studies reporting on bone marrow aspirate or autografts for non-orthopedic indications were also excluded. Results: After removal of duplicates, 5981 studies were identified. After screening, 85 studies remained for full-text assessment, and 15 studies qualified for the meta-analysis with a total of 2296 bone grafts.1557(67.8%) were calcaneal grafts, 625 (27.2%) were proximal tibial grafts, and 114 (5%) were distal tibial grafts. The mean age of all patients was 52.43+-16 [CI=51.77-53.08] years. The mean follow-up duration was 1.86+-1.70[CI=1.79-1.93] years. The primary surgery was reported for 2129 grafts(92.7%).Out of those, foot and ankle procedure represented 97.4% of the procedures. In calcaneal bone grafts, there were 28 cases of chronic pain [1.97%, CI:1.10-2.50%, I2=66%], 5 fractures [0.32%, CI:0.10-0.60%, I2=0%], 20 sural neuritis [1.28%, CI:0.70-1.80%, I2=0%), and no wound infections. In proximal tibial grafts there were 13 cases of chronic pain [2.08%, CI:1.01-3.2%, I2=34.5%], 1 fracture [0.16%, CI:0.10-0.50%, I2= 0%], and 3 superficial wound infections [0.48%, CI:0.10-1.01, I2=0%]. In the distal tibial grafts there were no cases of chronic pain or wound infections, 1 fracture [0.90%, CI:0.80-2.6%, I2=0%], and 5 saphenous neuritis [4.5%, CI: 0.70- 8.40%, I2=65%]. Conclusion: Calcaneal, distal tibial, and proximal tibial bone autografts are safe with a low rate of overall and major complications. We report an overall complication rate of 6.8%, which is less than half of that previously reported for iliac crest grafts. The authors recommend using distal lower extremity grafts for foot and ankle primary surgeries instead of iliac crest grafts when indicated. Clinical trials with large sample sizes are required.